Flipped classroom is not for every kind of student - Sobral, Sónia Rolland (2021)
Flipped classroom is a teaching strategy which has been greatly studied and utilized in various types and areas of teaching. Basically, it means that classes start being taught reverse to traditional classes. The teacher or instructor sends contents to students before lectures, adding the fact that students must study the subject matter before attending class. The advantages are clear: the time that each class takes with the teacher and classmates starts being used not to explain the subject, but for more complex questions which may be put only after clear knowledge of the subject. For this teaching strategy to work it is necessary that students do their homework, and that the teacher sends the correct and interesting study materials to students. In a phase of state of emergency-teaching or mixed teaching (presently and distance) caused by the COVID-19 global pandemic, flipped classroom started being much more used, namely in higher education and in areas such as IT. In this article we analyse 78 students of two IT courses, finding what type of students consulted the study materials sent by the teacher before lectures: we compare the characteristics of students, namely gender, age, course, attendance to classes (synchronous distance classes and laboratory classes at the university), as well as final classifications (divided into 4 levels and dropout). Thus, we will get to know for which type of students the effective use of the flipped classroom strategy may cause efficient learning and who are the students who will never do their previous homework.